Hybrid erbium-doped fiber laser-pressure sensor utilizing ring cavity - Abdullah F.; Idris S.M.; Jamaludin M.Z.; Al-Mansoori M.H. (2023)
This paper presents a hybrid erbium-doped fiber laser-pressure sensor system (HEDFL-PS) in a ring cavity configuration. The fiber laser sensor utilized an intracavity Bragg grating as pressure transducer and reflector. The HEDFL-PS can be used as a single wavelength high power laser or a high pressure sensor. The HEDFL-PS was tested using a shock tube facility and was able to measure up to 10 bar of static pressure. The sensor system shows solid linear response with sensitivity of 0.125 nm/bar and is stable over 30 min with negligible variation in output power and wavelength. Pleiades Publishing, Ltd. 2011.